Tropical insectivorous birds’ predation patterns that promote forest–farmland trophic connectivity for integrated top–down pest biocontrol - Nickson Erick Otieno; Nickson Erick Otieno; Jonathan Mukasi (Frontiers in Environmental Science, 2023)
Although conversion of natural forest to agriculture can negatively impact biodiversity in many ways, some affected species may respond by dispersing across the forest–farmland eco-zone, thereby facilitating functional connections through food-web interactions beneficial to crop production and forestry. This study examined patterns of Lepidoptera (butterflies and moths), Hemiptera (bugs), and Coleoptera (beetles) herbivory, and insectivorous bird predation within forest-adjacent farms in western Kenya, and how these processes trophically connect the two ecosystems to promote pest biocontrol. Through δ13C and δ15N stable isotope analyses, proportions of maize, farmland legumes and forest trees in pest diets, and pest-prey in bird’s diets were estimated. Birds’ habitat associations and diet specializations’ influence on pest consumption and basal plant carbon levels in birds’ tissues were determined to evaluate birds’ pest-biocontrol potential. Maize was the mostly consumed plant especially by Lepidoptera, but forest trees were peimarily consumed by Coleoptera and Hemiptera. In turn, Lepidoptera were mainly consumed by forest-associated birds, whereas Hemiptera and Coleoptera were mostly consumed by farmland-associated birds. Thus, birds showed cross-habitat pest consumption tendencies, though diet-specialization was unimportant in predicting those tendencies. Muscicapidae (flycatchers and allies); Hirundinidae (swifts and swallows); Motacillidae (pipits and wagtails); and Ploceidae (weavers) birds showed the highest contributory potential for pest biocontrol of Lepidoptera pests, but Estrildidae (manikins and waxbills), Muscicapidae, and Malaconotidae (boubous and gonoleks) birds showed the best potential against Hemiptera and Coleoptera. Furthermore, more maize basal carbon was assimilated by forest-associated compared to farmland-associated birds, whereas most basal carbon from farmland legumes and forest trees were assimilated by farmland birds, suggesting that unlike pest-prey choice, basal plant carbon pathways to avian insectivorous consumers did not strongly mirror birds’ habitat associations. Lepidoptera and Hemiptera were potentially the most significant interhabitat trophic connector arthropods, and for birds, Muscicapidae, Ploceidae, and Estrildidae. These findings show that such functional connectivity may be enhanced through increasing structural cover elements that promote insectivorous birds’ dispersal between farmland and adjacent forests to boost their pest-regulation ecosystem service contribution. The results serve to inform effective management practices by agronomists, foresters, and land-use planners toward promoting landscape-scale-integrated pest management for sustainable agriculture and biodiversity conservation.